Application of Dermatology Life Quality Index‐Relevant (DLQI‐R) in patients with moderate‐to‐severe plaque psoriasis treated with tildrakizumab - Philip Laws; Kristian Gaarn Du Jardin (Wiley, 2023)
Abstract Background Tildrakizumab is an interleukin‐23p19 inhibitor approved for the treatment of moderate‐to‐severe plaque psoriasis. The new Dermatology Life Quality Index (DLQI)‐Relevant (DLQI‐R) scoring system avoids the bias in the not relevant response option of the DLQI by adjusting the total score to the relevant items. Objectives To assess the impact of tildrakizumab on health‐related quality of life (HRQoL) in patients with moderate‐to‐severe psoriasis in the reSURFACE 2 phase 3 trial as measured with the original DLQI scoring and with the new DLQI‐R. Methods Post hoc analysis of adult patients with moderate‐to‐severe plaque psoriasis from a double‐blinded, randomized, controlled, 52‐week trial. The presented analysis is based on observed cases. Results At baseline, 31.9%/33.6%/40.0% of patients on tildrakizumab 100 mg/tildrakizumab 200 mg/placebo had ≥1 DLQI item marked as 'not relevant'. The most frequently 'not relevant' items were 'sport' (14.0%/13.9%/15.5%) and 'working/studying' (13.4%/11.3%/12.9%), in the tildrakizumab 100 mg/tildrakizumab 200 mg/placebo groups, respectively. At baseline, 68.1%/73.0%, 60.3%/63.2% and 62.6%/65.8% of patients on tildrakizumab 100 mg, tildrakizumab 200 mg and placebo had a DLQI > 10/DLQI‐R > 10, respectively. Mean DLQI/DLQI‐R scores at baseline were 14.8/15.5, 13.3/14.1, and 14.1/15.0 in the tildrakizumab 100 mg, tildrakizumab 200 mg and placebo groups, respectively. The median change from baseline in both DLQI and DLQI‐R scores at Week 12 was greater in the tildrakizumab 100 mg and 200 mg groups versus placebo (−10.0, −9.0, −1.0 and −11.0, −9.3, −1.1, respectively). At Week 52, the median change from baseline in DLQI/DLQI‐R was −13.0/−14.0 and −10.0/−10.1 in the tildrakizumab 100 mg and 200 mg groups, respectively. Conclusions Treatment with tildrakizumab resulted in significant and sustained improvements in HRQoL up to Week 52 in patients with moderate‐to‐severe psoriasis. The DLQI‐R provides a more unbiased HRQoL assessment ensuring that those who are unable to work/partake in sport have a truer assessment and opportunity for treatment.